Arginase activity and nitric oxide levels may be considered as tumor markers in breast cancer - Iclal GEYIKLI, Nurdan OZLU CEYLAN, Celalettin CAMCI (Journal of Applied Pharmaceutical Science)
To investigate the relationship of breast cancer with serum arginase activity and nitric oxide levels. Arginase (L-arginine ureohidrolase, EC. 3.5.3.1) is the last enzyme of urea cycle which converts arginine into urea and ornithine. nitric oxide, a product of L-arginine and nitric oxide synthetase reaction, is a hormone, a reactive oxygen species, neurotransmitter, mediator, cytoprotective molecule, and the only endogenous molecule that acts as a cytotoxic molecule. This study was done at Gaziantep University Research Hospital with 30 breast cancer patients (30-77) and with 34 healthy people (30-75) to diagnose breast cancer. The majority (n=28) was ductal while the rest were medullary and papillary cancers. Serum arginase activity was measured by thiosemicarbazide diasetilmonoksim urea method in U/L that was modified. Also, serum nitric oxide levels were measured by the Griess method in terms of mmol/L. Serum arginase activity was determined as 17.8±2.5 (X±SE) U/L in the patient group and 6.8±0.9 U/L in the control group; the cancer patients showed a significant increase (t=3,649, p
Keywords: Arginase,cancer,nitricoxide